Structural Stability of Vacancy and Substitutional Defects in g-GaN: A First-Principles Study - Fadlliyana, Malika; Fajariah, Nurul; Nurwantoro, Pekik; Prayogi, Harmon; Purnawati, Diki; Oktavina, Cristina Wulan; Nugraheni, Ari Dwi; Sholihun, Sholihun (Trends in Sciences, 2024)
Herein, the first-principles calculations of defected monolayer graphene-like gallium nitride (g-GaN) were elucidated. The optimized geometric revealed that the nearest-neighbor distances of N-N (between N atoms) and Ga-Ga (between Ga atoms) were narrowing in most configurations. Interestingly, the VGa has a similar atomic symmetry as the pure g-GaN, which is D3h. Most defected configurations are degraded into C2V symmetries, while the Stone-Wales configuration has the lowest symmetry of CS. The formation energies of VNa systems are lower, which implies better energetic stability. For the divacancies, the VGa system is more stable than the VNa system. Moreover, the Stone-Wales configuration is energetically more stable than the interchange configuration. Furthermore, the reaction coordinates represent the geometric evolution of each defected system. The result revealed that the N-atoms are consistent with moving outward while the Ga-atoms move inward only for monovacancies and divacancies configurations. In contrast, the N-atoms move inward while the Ga-atoms move outward for substitutions, interchanges, and Stone-Wales configurations. We believe that this finding will be beneficial as the groundwork for future 2D g-GaN-based semiconductor devices. HIGHLIGHTS The VNa defective system is more stable than the VGa system in monovacancies and substitutions. The VGaGa defective system is more stable than the VNa system in divacancies. The Stone-Wales system is a stable configuration with a Cs symmetry. GRAPHICAL ABSTRACT